2020
DOI: 10.3389/fneur.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Long-Term Behavioral Disturbances and Provided Care After Traumatic Brain Injury

Abstract: Introduction: Behavioral disturbances are found in 50-60% of traumatic brain injury (TBI) survivors with an enormous impact on daily functioning and level of recovery. However, whether typical profiles can be distinguished and how these relate to provided care is unclear. The purpose of this study is to specify the characteristics of behavioral disturbances in patients with various severity of TBI and the impact on functional outcome. Furthermore, the pathways of care after hospital discharge for patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…This study shows BoC in a considerable percentage of SAH and TBI patients, which is in accordance with previous research (Al-Khindi et al, 2010;Hicks et al, 2017;Timmer et al, 2020). Problems in impulsivity and aggression were experienced by 13.2% of participants, while 54.4% of participants experienced problems in social monitoring and empathy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study shows BoC in a considerable percentage of SAH and TBI patients, which is in accordance with previous research (Al-Khindi et al, 2010;Hicks et al, 2017;Timmer et al, 2020). Problems in impulsivity and aggression were experienced by 13.2% of participants, while 54.4% of participants experienced problems in social monitoring and empathy.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with TBI and SAH have a higher risk of both PTSD and depression, which is related to increased aggression (Hedlund, Zetterling, Ronne-Engström, Carlsson, & Ekselius, 2011;Perroud, Baud, Mouthon, Courtet, & Malafosse, 2011;Stein et al, 2019;Taft, Creech, & Murphy, 2017). That aggression is not solely related to the severity and location of brain damage is supported by a recent study of Timmer et al (2020), who showed that anger (49%), verbal aggression (11%), and physically violent behavior (1.9%) occur in mild TBI patients who have very limited to no brain damage. In comparison, moderate-to-severe TBI patients experienced similar amounts of anger (40%), verbal aggression (10%), and physically violent behavior (.8%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As for sex differences, a recent study aimed at characterising the demographic, social and economic profile of patients with TBI in Brazil showed that men were hospitalised almost 3.5 times more frequently for TBI than women and that the incidence of TBI in the male population was 102/100 000/year. 69–71 …”
Section: Discussionmentioning
confidence: 99%
“…With regard to the emotional domain, we found a post-injury irritability score as a predictor of IR after sustaining an mTBI at an older age. Previous studies on adults with mTBI identified irritability among post-traumatic complaints that can persist for longer than 1 year ( 46 , 47 ) and are associated with its severity ( 48 ). Interestingly, Yang et al ( 49 ) studied adults with mild- and moderate-to-severe TBI and found that annoyance (i.e., an aspect of irritability) was self-reported by patients with mTBI but remained unnoticed by their caregivers.…”
Section: Discussionmentioning
confidence: 99%